Association of Admission Temperature and Outcome among Neonates with Sepsis in a Tertiary Care Hospital (Dhaka Shishu (Children) Hospital Journal, 2020)
Background: Neonatal sepsis is one of the major causes of mortality in neonates. Hypothermia is also an important contributing factor of neonatal mortality. Neonates with sepsis can present with normal temperature, hypo or hyperthermia.Objectives: This study was design to find out the pattern of temperature on admission and its association with mortality among neonates admitted with sepsis.Methods: This cross-sectional study was conducted from September 2017 to April 2018 in the Department of Neonatal Medicine and NICU, Dhaka Shishu (Children) Hospital. Neonates up to thirty days of age, diagnosed as probable sepsis were enrolled. On admission, axillary temperature was recorded for 3 minutes and neonates were categorized according to the recorded temperature. Neonates were classified as early onset sepsis (EOS) and late onset sepsis (LOS) according to the age of onset of the sepsis. Outcome was also recorded. Statistical analysis was done by SPSS program version 25. Chi-square (X2) test was done to determine the association and p value,